The Drama of the Contemporary Man in the Play "Birthday" by Harold Pinter - YELINYAN, NAIRA (Bulletin of Yerevan University B: Philology, 2021)
After the World War II England was in spiritual crisis, and Pinter succeeded in drawing the tragic picture of a contemporary man describing in exact colours the crisis and inner search of his century. The playwright pictures those critical states in which the individuals find themselves: the human being is lonely, troubled, alienated and secluded from the society, confused and frightened in the enemy world, he is always in a search of a home – a safe shelter. Pinter has reflected the complex and controversial inner world of the human being. He succeeded in emphasizing the drama of an individual, their views and perceptions that are well presented in Pinter’s ‘Birthday Party’.